Is there a critical rate of torque development? - Abdalla, Leonardo Henrique Perinotto [UNESP] (2025)
The objective of this study was to test the hypothesis that neuromuscular fatigue influences the rate of torque development (RTD) in a similar manner to isometric torque. Nine men participated in this study and performed 5-min all-out isometric tests for knee extensors (KE) and plantar flexors (PF) muscles, to determine the end-test torque (ET) and the critical rate of torque development (critical RTD). Additionally, participants performed submaximal constant-torque tests to task failure for KE and PF muscles. Both maximal voluntary contraction and RTD exhibited hyperbolic behavior and reached an asymptote at the end of the 5-min all out isometric test with similar relative values (KE 29.5 ± 5.6% MVC and PF 50.9 ± 2.9% MVC and KE 25.1 ± 3.6 to 28.5 ± 4.4% RTD and PF 48.4 ± 6.5 to 52.4 ± 5.8% RTD). However, both % MVC and % RTD were statistically different between muscle groups (P < 0.05), even when normalized by muscle volume (P < 0.05). Torque and RTD after the constant-torque test were similar to the values of ET and critical RTD (P > 0.05), respectively. In this study, it was observed that neuromuscular fatigue affects RTD and torque similarly, with the magnitude of this effect varying according to the muscle size.